ANALISIS INTEREST RATE PASS-THROUGH PADA MEKANISME TRANSMISI KEBIJAKAN MONETER INDONESIA - Risna Amalia Hamzah; Handri Handri (Universitas Batanghari Jambi, 2017)
This reseach aimed to evaluate the performance of monetary policy, toexamine and test the magnitude of the response rates on deposits and bank loans to the money market interest rate, and how fast adjustment of the interest rate of deposits and loans in response to changes in money market interest rates. The performance evaluation of the level of adjustment of interest rate pass-through is done by testing the coefficient of adjustment of the interest rate deposits and loans in response to changes in money market interest rates. The object of this reseach is reported in interest rates interbank money market (rPUAB) and bank interest rates (loans and deposits) of all commercial banks in Indonesia, the data used in the form of a row of monthly time (monthly time series) of the annual report of Bank Indonesia and SEKI ( Economic and Financial statistics Indonesia), in the period 2005-2016. The method used in this research is the Autoregressive Distributed Lag (ARDL) for calculating the amount of long-term coefficients and Error Correction Model (ECM) -ARDL for calculating the amount of short-term coefficients. We find of the analysis indicate a change of monetary policy in the short term through the interest rate channel with its operational targets interest rates interbank money market (interbank) did not respond in full by the rates on deposits and loans in commercial banks in Indonesia, represented by the value of the degree of pass- through which less than 1 and there is a tendency that the longterm interest rates on loans and deposits experienced incomplete pass-through, then interest rates on consumer loans and deposits of 24 months has the speed of the slowest, which means consumer loans and deposits of 24 months in Indonesia unresponsive to changes in interbank rates. keywords: ARDL, ECM, Interest Rate pass-through, PUAB.